‘Paying the ultimate price’: Zimbabwe and the liberation of South Africa, 1980–1994 - Bhebe, Ngwabi M.; Mazarire, Gerald C. (Unisa Press, 2016)
Focuses on the historical significance of African solidarity in as far as South Africa’s struggle for national liberation is concerned. This is done in order to challenge the notion and widely shared prejudice permeating South African historiography; that while South Africa is geographically a part of the African continent; its history is not integral to that of the continent but to the history of its European colonial powers. To debunk this offshore island view about South Africa in Africa the volume analyses the relationship which existed between the Organisation of African Unity and the South African liberation movements, the ANC and the PAC. It also highlights the fraternal ties that bound these liberation movements to countries such as Ghana, Ethiopia, Tanzania, Zambia, Botswana, Algeria, Lesotho, Nigeria, Egypt, Botswana, Zimbabwe and the Caribbean region.